Improvement of Creative Ability and its Mechanisms - Marhabo Yusufovna Yakubova (Web of Journals Publishing, 2023)
Today creativity is the important criterion of the person, the factor of his complete development. Therefore, in the state educational policy of creativity - at intellectual level, naturally, on an informative basis, the especial attention now is given to active creativity. In the educational policy of Uzbekistan among development of the basic qualities and abilities trained are allocated creative - potential of the person with special attention to intellectual-creative thinking. That is quite lawful, as the new thinking - courageous, original, creative, initiative, constructive, is innovative-innovative today is required.
Keywords: Original, creative, initiative, constructive, innovative, education, develop ment, basic, quality, level, thinking.